Faktor Prediktor Pemberian ASI Eksklusif Pada Ibu Menyusui Wilayah Kerja Puskesmas Mangasa Kota Makassar - Zulmuawinah, Zulmuawinah; Samsualam, Samsualam; Noer, Nuraeni (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Exclusive breastfeeding is known as one of the most powerful against child survival, growth and development. There is nothing Exclusive breastfeeding in the region ranged from 60-70% Mangasa Clinics every year, which should reach the target of 80%. Yet the achievement target Exclusive breastfeeding due to several factors. This research aims to analyze the anatomy of breast abnormality, factor support husband, granting KIE Lactation, knowledge, children's health and work history against Exclusive breastfeeding. Analytic Observational research methods with the design of Cross-Sectional Study. Research is done in the area of Employment Clinics Mangasa Makassar city. The sample in this research the entire mother who has a baby aged 6-12 months. The instruments used are the now (questionnaire). Data analysis using univariate analysis, bivariate analysis, multivariate analysis (logistic regression) The results of this study showed that mothers who provide Exclusive BREAST MILK as much as 66.7%. Anatomical abnormalities of the breast (p B Exp 0.028 < 3.666), support the husband (p > 0.844), knowledge (p B Exp 0.022 < 3.361), KIE Lactation (p 0.007 B Exp < 0.075), childbirth/health history (p > 0,195), and occupation (p 0.002 B Exp < 6.783). There is a significant relationship between anatomic abnormality of the breast, job, granting KIE lactation, and knowledge with exclusive breastfeeding p < 0.05. There was no significant relationship between the support of her husband and childbirth/health history with exclusive breastfeeding. The dominant factor and the work to exclusive breastfeeding